1994
DOI: 10.1037/0735-7044.108.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Rhinal cortex lesions and object recognition in rats.

Abstract: Rats with bilateral lesions of lateral entorhinal cortex and perirhinal cortex were tested on a nonrecurring-items delayed nonmatching-to-sample (DNMS) task resembling the one that is commonly used to study object recognition in monkeys. The rats were tested at retention delays of 4 s, 15 s, 60 s, 120 s, and 600 s before and after surgery. After surgery, they displayed a delay-dependent deficit: They performed normally at the 4-s delay but were impaired at delays of 15 s or longer. The addition of bilateral am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
276
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(304 citation statements)
references
References 29 publications
(73 reference statements)
26
276
2
Order By: Relevance
“…an object encountered during a previous trial and a new object that the animal has never encountered before). Some early studies have shown that discrimination between stimuli can occur independently of the perirhinal cortex: combined lesion of the rhinal region and area TE did not significantly impair rats on a visual discrimination task and ablation of the rhinal region does not impair rats in the acquisition of an object discrimination task (Mumby and Pinel, 1994). Both these studies suggest that stimulus discrimination may not be one of the perirhinal cortex's primary functions even if it requires an ability to discriminate stimuli in order to perform its role as a novelty detector.…”
Section: The Perirhinal Cortex and Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…an object encountered during a previous trial and a new object that the animal has never encountered before). Some early studies have shown that discrimination between stimuli can occur independently of the perirhinal cortex: combined lesion of the rhinal region and area TE did not significantly impair rats on a visual discrimination task and ablation of the rhinal region does not impair rats in the acquisition of an object discrimination task (Mumby and Pinel, 1994). Both these studies suggest that stimulus discrimination may not be one of the perirhinal cortex's primary functions even if it requires an ability to discriminate stimuli in order to perform its role as a novelty detector.…”
Section: The Perirhinal Cortex and Perceptionmentioning
confidence: 99%
“…The main behavioural role identified for the perirhinal cortex is recognition memory (Mumby and Pinel, 1994;Suzuki, 1996;Liu and Bilkey, 2001;Mumby et al, 2002bMumby et al, , 2007Winters and Bussey, 2005a;Hannesson et al, 2005;Albasser et al, 2009;Brown et al, 2010) but roles for the perirhinal cortex in fear conditioning (Suzuki, 1996) and in spatial memory-related tasks (Wiig and Bilkey, 1994;Glenn et al, 2003;Abe et al, 2009) will also be discussed. Additionally, we will review the developing evidence for the perirhinal cortex in perceptual processing that is typically not addressed in the wider learning and memory literature (Bussey et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki, Miller, and Desimone (1997) extended this result to demonstrate that this stimulus-specific firing persisted across multiple intervening stimuli. Buffalo, Reber, and Squire (1998) showed that people with lesions to the perirhinal cortex showed deficits of recognition memory over delays as short as 6 s. Mumby and Pinel (1994) showed that rats with damage to entorhinal and perirhinal cortex were impaired on delayed non-match to sample (DNMS) of trial-unique object at delays as short as 15 s. Otto and Eichenbaum (1992) showed no deficit in a continuous delayed non-match task from fornix transection, but showed a deficit from combined perirhinal/entorhinal lesions at delays of 30 s. This not only points to a role for the parahippocampal regions in memory on the time scale of the recency effect in free recall, but argues against a role of the hippocampus in such processes. Murray and Mishkin (1998), showed that lesions to the amygdala and hippocampus that spared rhinal cortex did not have an effect on DNMS performance, whereas a comparable study showed a severe impairment from rhinal cortex lesions at delays as short as tens of seconds (Meunier, Bachevalier, Mishkin, & Murray, 1993 The first suggestion comes from the finding that hippocampal damage is associated with a disruption of memory for items from the early part of the serial position curve.…”
Section: The Context T a Imentioning
confidence: 99%
“…At 1 week after saline or drug treatment, the animals were exposed to a novelty preference task of OR (Myhrer, 1988;Mumby and Pinel, 1994;Tang et al, 1999). The OR task required that the rats recall which of two small objects they had previously been exposed to.…”
Section: Behavioral Proceduresmentioning
confidence: 99%